2020
DOI: 10.3390/cells9092118
|View full text |Cite
|
Sign up to set email alerts
|

How Relevant Are Bone Marrow-Derived Mast Cells (BMMCs) as Models for Tissue Mast Cells? A Comparative Transcriptome Analysis of BMMCs and Peritoneal Mast Cells

Abstract: Bone marrow-derived mast cells (BMMCs) are often used as a model system for studies of the role of MCs in health and disease. These cells are relatively easy to obtain from total bone marrow cells by culturing under the influence of IL-3 or stem cell factor (SCF). After 3 to 4 weeks in culture, a nearly homogenous cell population of toluidine blue-positive cells are often obtained. However, the question is how relevant equivalents these cells are to normal tissue MCs. By comparing the total transcriptome of pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 82 publications
0
19
0
Order By: Relevance
“…The authors reported that the reason for the discrepancy was a major difference between mouse and human MCs since only the latter depended on ERK for MRGPRX2-driven β-hexosaminidase and histamine release [54]. This was a notable finding since MC research is heavily biased towards the mouse, and makes vivid use of murine BMMCs, which differ not only from humans, but also from other murine MC types [72]. In our study, ERK involvement was found for both ex vivo and precultured skin MCs, yet it was stronger in the latter, suggesting that the cellular environment also plays a role in dictating the significance of ERK.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported that the reason for the discrepancy was a major difference between mouse and human MCs since only the latter depended on ERK for MRGPRX2-driven β-hexosaminidase and histamine release [54]. This was a notable finding since MC research is heavily biased towards the mouse, and makes vivid use of murine BMMCs, which differ not only from humans, but also from other murine MC types [72]. In our study, ERK involvement was found for both ex vivo and precultured skin MCs, yet it was stronger in the latter, suggesting that the cellular environment also plays a role in dictating the significance of ERK.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, a pro- and anti-tumor effect was observed in the same tumors ( 67 , 113 , 114 ). In addition, differences in MC phenotypic and functional responses between mice and humans have been well documented ( 111 , 115 123 ). For example, Fcγ receptor expression and functional responses mediated by them on mouse and human MCs and monocytes are vastly different ( 124 126 ).…”
Section: In Cancer; Evidence For Both Anti- and Pro-tumor Rolesmentioning
confidence: 99%
“…The transcripts for the granule proteases are the most highly expressed transcripts in the mature MC where the expression levels can be in the range of several percent of the total transcriptome ( 1 , 16 , 22 ). In addition to MC tryptase and chymase, serine proteases belonging to the same family of trypsin/chymotrypsin related serine proteases have in mammals also been identified in basophils, neutrophils, cytotoxic T cells and natural killer (NK) cells but not in B cells, macrophages, red blood cells, platelets or dendritic cells and only at relatively low levels in eosinophils.…”
Section: Introductionmentioning
confidence: 99%